2019
DOI: 10.1002/jee.20263
|View full text |Cite
|
Sign up to set email alerts
|

Design by taking perspectives: How engineers explore problems

Abstract: Background Problem exploration includes identifying, framing, and defining design problems and bounding problem spaces. Intentional and unintentional changes in problem understanding naturally occur as designers explore design problems to create solutions. Through problem exploration, new perspectives on the problem can emerge along with new and diverse ideas for solutions. By considering multiple problem perspectives varying in scope and focus, designers position themselves to increase their understandings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 80 publications
3
43
0
Order By: Relevance
“…As discussed in Hay et al (2017), there is a need for larger-scale, quantitative experiments in design to build upon small-scale, qualitative studies. AEDI can contribute to addressing this challenge in the context of exploratory ideation, where research topics include the nature of exploration patterns (Murray et al 2019) and their link with solution novelty (Finke, Ward, and Smith 1992) and other attributes of design outcomes (Studer et al 2018). We used AEDI in an fMRI study of professional product design engineers, where an output-based analysis approach was necessitated by constraints on verbalisation and physical behaviour inside the MRI scanner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in Hay et al (2017), there is a need for larger-scale, quantitative experiments in design to build upon small-scale, qualitative studies. AEDI can contribute to addressing this challenge in the context of exploratory ideation, where research topics include the nature of exploration patterns (Murray et al 2019) and their link with solution novelty (Finke, Ward, and Smith 1992) and other attributes of design outcomes (Studer et al 2018). We used AEDI in an fMRI study of professional product design engineers, where an output-based analysis approach was necessitated by constraints on verbalisation and physical behaviour inside the MRI scanner.…”
Section: Discussionmentioning
confidence: 99%
“…For instance: a waste monitoring system (S) to discourage people from creating waste (P); a composting system (S) to facilitate waste recycling (P); and single-portion food packaging (S) to discourage excessive food purchases (P). This may be termed exploratory ideation, and is particularly associated with the early, creative stages of conceptual design (Dorst and Cross 2001;Murray et al 2019) where the problem tends to be fuzzy and abstract (Gero and McNeill 1998;Suwa, Gero, and Purcell 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst proponents of problem solving view designing as a search process transforming knowledge to address a fixed problem, the reflective paradigm offers a different perspective. Here, design problems and solutions are subject to reinterpretation and reformulation in a process shaped by the design context (Gero 1990;Lloyd & Scott 1994;Dorst & Dijkhuis 1995;Murray et al 2019). Most recently, the 1990s-2000s have seen designing formalized as a situated, exploratory, and evolutionary process by Goldschmidt (1991), Maher et al (1996), Gero & Kannengiesser (2004) and others.…”
Section: A Brief Historymentioning
confidence: 99%
“…The study found that gender sensitivity was not much at the undergraduate level, whereas gender-based exclusion and discrimination was significant at the Master level. Systematic patterns in problem exploration in the early design phases of mechanical engineers were investigated by assigning design tasks to both students at various levels of undergraduate mechanical engineering studies and working mechanical engineers (Murray et al, 2019). The participants approached the real-world design…”
Section: Ffmentioning
confidence: 99%